Periodically harvested closures require full protection of vulnerable species and longer closure periods. (November 2016) - Goetze, Jordan; Langlois, Tim; Claudet, Joachim; Januchowski-Hartley, Fraser; Jupiter, Stacy D.
Abstract: Periodically harvested closures (PHCs) are small fisheries closures with objectives such as sustaining fisheries and conserving biodiversity and have become one of the most common forms of nearshore marine management in the Western Pacific. Although PHCs can provide both short-term conservation and fisheries benefits, their potential as a long-term management strategy remains unclear. Through empirical assessment of a single harvest event in each of five PHCs, we determined whether targeted fishes that differ in their vulnerability to fishing recovered to pre-harvest conditions (the state prior to last harvest) and demonstrated post-harvest recovery benefits after 1 year of re-closure. For low and moderately vulnerable species, two PHCs provided significant pre-harvest benefits and one provided significant post-harvest recovery benefits, suggesting a contribution to longer-term sustainability. PHCs with a combination of high compliance and longer closing times are more likely to provide fisheries benefits and recover from harvest events, however, no benefits were observed across any PHCs for highly vulnerable species. We recommend PHCs have longer closure periods before being harvested and species that are highly vulnerable to fishing (e.g. large species of; grouper, wrasse and parrotfish) are avoided during harvests to avoid overexploitation and increase the sustainability of small-scale fisheries. Highlights: Periodically harvested closures (PHCs) can increase targeted fish biomass. PHCs will need at least 3 years of closure to provide long-term benefits. Highly vulnerable species will not benefit from PHC management. PHCs should be combined with conventional fisheries management strategies. No-take marine reserves should be used for conservation rather than PHCs.